A Day of Learning at Publication Coaching Event - Norhidayah, Abdull (Faculty of Industrial Sciences and Technology (FSTI), 2024)
In Pantai Cempaka, Kuantan, on May 18, 2024, a group of 21 staff from Occupational Safety and Health research cluster gathered at Dewan Permata Camar for an inspiring event titled "Publication Coaching: From Results to Submission in 8 Hours" led by Assoc. Prof. Dr. Mohd Herwan Sulaiman.